Van Dhan Vikas Kendras (VDVKs) on Tribal Women Entrepreneurship and Empowerment in Alluri Sita Rama Raju District of Andhra Pradesh - Moses, G.Sharon; Rani, Seedari Ujwala; Reddy, P. Pedda Nagi; Naidu, G. Mohan; Kishore, M. Ravi; Naik, B. N. Sandeep; Rao, P. Joga (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during March to May month of year 2025 at Alluri Sita Rama Raju District, Andhra Pradesh, India to study the impact of VDVK on women entrepreneurship and empowerment in study area. The entrepreneurship activities facilitated by Van Dhan Vikas Kendra have significantly empowered tribal women across Chintapalli, Paderu and G. Madugula mandals in the Alluri Sitarama Raju district. The sample size was 80 VDVK beneficiaries and 80 non-beneficiaries. The approaches like before and After, with and Without and Women empowerment Index were applied to collected primary data. The major minor forest produce marketed by VDVK are Adda leaf plates, De seeded tamarind, Hill brooms, and Soapnuts. It was analysed that Average annual income of beneficiaries doubled from Rs. 31,000 to Rs. 59,912.55 and employment man-days rose from 130 to 310, largely due to 210 days generated by VDVK activities. Food and non-food consumption increased from Rs. 23,000 to Rs. 37,200 and Rs. 8,000 to Rs. 24,800, respectively, reflecting improved living standards. Beneficiaries showed significantly higher scores across activity, knowledge, health, autonomy and social domains with a Women Empowerment Index Value 0.69 compared to 0.45 among non-beneficiaries. These findings affirmed that structured institutional support through VDVKs fosters holistic empowerment, bridging gender and economic gap could contribute significantly to inclusive and sustainable development in tribal areas.